Determinants of internationalization of SMEs automation in Penang – networking, management attitude, entrepreneurial orientation and marketing characteristics - Seow, Kweng Tian (2021)
This study empirically investigates the relationship between determinants – networking, management attitude, entrepreneurial orientation, and internationalization of SMEs in the automation industry of Penang, Malaysia, with marketing characteristics as moderator. The study is based on the notion of using networking to obtain resources and access market opportunities; and positive management attitude and entrepreneurial orientation as strategic intangible resources, as well as adoption of marketing characteristics to boost internationalization of firms in the automation industry. A total of 108 survey questionnaires were used for analysis by using statistical package of social sciences (SPSS) version 23 and partial least squares-structural equation modelling (PLS-SEM) SmartPLS3.0. Research findings empirically established that networking and management attitude have positive significance influence on the internationalization of SMEs in the automation industry of Penang. While positive significance influence of entrepreneurial orientation on the internationalization of SMEs in Penang’s automation industry lacks statistical support. As for the assessment of marketing characteristics as moderator, the effect of marketing characteristics on the relationship between networking and management attitude and internationalization of SMEs in the automation industry of Penang are established statistically. However, the results showed that this study could not establish support on the effect of marketing characteristics as moderator on the relationship between entrepreneurial characteristics and internationalization of SMEs in the automation industry of Penang. Thus, this study is critical for Malaysia’s SMEs to adequately network with relevant partners, develop right management attitude and properly exploit marketing characteristics of host countries, in order to enhance internationalization. In addition, the study highlighted several limitations and suggestions for future research direction.